ChatGPT and Large Language Models: Unraveling Multifaceted Applications, Hallucinations, and Knowledge Extraction - Hamarashid, Hozan Khalid; Karim, Lina Tofiq; Muhammed, Danial Abdulkareem (Universitas Negeri Semarang, 2023)
Recent strides in artificial intelligence have given rise to large language models (LLMs), particularly those adepts at deep learning and human language processing. These innovative models, exemplified by ChatGPT, leverage robust transformer algorithms to comprehend and generate text like human language. Despite their prowess, LLMs are prone to hallucinations, presenting inaccuracies as facts. Unraveling the retained knowledge within these models proves challenging. This paper delves into the multifaceted use of ChatGPT as a large language model, exploring its capability to generate concise summaries from extensive text and addressing the phenomenon of hallucinations. Furthermore, the study showcases ChatGPT's proficiency in extracting crucial information from large datasets, such as revealing the top ten cited papers in the realm of artificial intelligence. The manuscript not only illustrates the practical application of artificial intelligence in research but also emphasizes the importance of utilizing these models effectively, particularly in the context of conducting precise literature reviews. Abstrak Kemajuan baru-baru ini dalam kecerdasan buatan telah melahirkan model bahasa besar (LLM), terutama yang mampu memahami pembelajaran mendalam dan pemrosesan bahasa manusia. Model-model inovatif ini, yang diwakili oleh ChatGPT, memanfaatkan algoritma transformer yang mampu untuk memahami dan menghasilkan teks seperti bahasa manusia. Meskipun memiliki kemampuan, LLM rentan terhadap halusinasi, yakni menyajikan ketidakakuratan sebagai fakta. Menggali pengetahuan yang terdapat pada model-model tersebut sangat menarik. Artikel ilmiah ini menggali penggunaan serbaguna ChatGPT sebagai model bahasa besar, mengeksplorasi kemampuannya untuk menghasilkan ringkasan singkat dari teks yang luas dan mengatasi fenomena halusinasi. Selain itu, penelitian ini menyajikan kemampuan ChatGPT dalam mengekstrak informasi penting dari kumpulan data besar, dalam hal ini mengkaji sepuluh artikel yang paling sering dikutip dalam ranah kecerdasan buatan. Artikel ilmiah ini bukan hanya menggambarkan penerapan praktis kecerdasan buatan dalam penelitian, melainkan juga menekankan pentingnya memanfaatkan model-model ini secara efektif, khususnya dalam konteks melakukan tinjauan literatur yang akurat.